Occurrence of fish larvae and juveniles in the bank waters at the mouth of the So estuary, Nam Dinh province - Thanh, Tran Trung; Ngoc, Ha Thi; Hau, Tran Duc (Academia Journal of Biology, 2017)
To examine the species composition and occurrence of larvae and juveniles of fish in the bank waters at the mouth of the So estuary in Nam Dinh Province, a seine net (1×4 m, 1 mm mesh-aperture) was used to sample monthly in early morning, around noon and late afternoon from November 2013 to October 2014. A total of 9274 larvae and juveniles (primarily postflexion larvae) of 45 species from 23 families and 9 orders were sampled. Of these species, Clupanodon thrissa was listed as a rare species in the Red Data Book in the EN category. Of the 9 orders, Perciformes was the most diverse in the number of the species and family, which comprised 66.7% and 56.5%, respectively. Larvae and juveniles appeared abundantly during rainy season, reaching a peak in May (an average of 516.6 individuals per haul), and the number of species was highest in July (17 species). The daily appearance of number of fish species in this area was depended on the water temperature, with highest in noon (30 species), followed by early morning (27 species) and late afternoon (26 species). The number of individuals was not depended on parts of the day but on water turbidity. Species that appeared abundantly occurred mostly a year-round, which initially indicate that this area plays an important role as a nursery ground for fishes during the early stages. Citation: Tran Trung Thanh, Ha Thi Ngoc, Tran Duc Hau, 2017. Occurrence of fish larvae and juveniles in the bank waters at the mouth of the so estuary, Nam Dinh province. Tap chi Sinh hoc, 39(2): 165-173. DOI: 10.15625/0866-7160/v39n2.8397 *Corresponding author: hautd@hnue.edu.vn Received 7 June 2016, accepted 20 March 2017